Prevalenza di atopia nella dermatite allergica da contatto professionale: confronto tra tecniche diagnostiche / Prevalence of atopic conditions in patients with occupational contact allergic dermatitis: comparison between diagnostic tools - Barbieri, Maria Teresa; Cocco, Maria Elisabetta; Cocco, Pierluigi (La Medicina del Lavoro, 2013)
Summary«Prevalence of atopic conditions in patients with occupational contact allergic dermatitis: comparison between diagnostic tools». Background: Occupational allergic contact dermatitis (OACD), to which atopy contributes to an as yet unspecified degree, accounts for a considerable number of work-related diseases. Objectives: We studied the prevalence of atopy in OACD patients. We also compared the ability of prick tests and specific IgE assays to detect it. Methods: In 329 patients diagnosed with OACD at the Occupational Medicine Unit of Cagliari University Hospital between 2000 and 2009, we aimed at detecting atopic conditions with prick tests and IgE assays specific for allergens most frequently responsible for atopic reaction. A kappa test was used to assess concordance between the two assays. The χ2 test for trend was used in the analysis of prevalence of atopy by age at diagnosis. Results: A positive response was more frequently detected with prick tests (35.9%) than the specific IgE assays (31%). IgE assays for all the allergens we tested were more frequently positive among males (p range=0.001-0.037). With either test, the highest observed prevalence of a positive response was to Dermatophagoides pteronyssinus. A significantly inverse trend with increasing age in the prevalence of positive reaction to Dermatophagoides pteronyssinus, Phleum pratense and Olea europaea (olive) allergens was also observed. The concordance between the two tests ranged between good (Dermatophagoides pteronyssinus, Phleum pratense and Olea europaea and moderate Artemisia vulgaris (mugwort) and Parietaria judaica. Conclusions: Our results showed a prevalence of atopic conditions in 31-35.9% of OACD patients. Results with the two assays were largely consistent, indicating that both prick tests and specific IgE assays are valid diagnostic tools for atopy.RiassuntoIntroduzione: La dermatite allergica da contatto (DAC) costituisce una quota importante delle patologie professionali, alla cui insorgenza contribuiscono, in misura ancora incerta, pre-esistenti stati di atopia. Obiettivi: Abbiamo valutato  la prevalenza di atopia in pazienti con diagnosi di DAC professionale, mediante prick test e dosaggio delle IgE specifiche. Metodi: In 329 pazienti con diagnosi  di DAC professionale posta presso la Struttura Complessa di Medicina del Lavoro dell’Azienda Ospedaliero-Universitaria di Cagliari tra il 2000 ed il 2009, è stata ricercata la risposta atopica mediante prick test e dosaggio delle IgE specifiche, la cui concordanza è stata valutata con test kappa. Il trend del tasso di prevalenza delle risposte positive in relazione all’età è stato studiato mediante χ2 per il trend. Risultati: La prevalenza di atopia è risultata più elevata in base alla positività ai prick test (35,9%) rispetto al dosaggio delle IgE specifiche (31%). La positività del dosaggio delle IgE è risultata significativamente più frequente nei soggetti di genere maschile per tutti gli antigeni testati (p range=0,001-0,037). La positività più frequentemente riscontrata con entrambi i test  è stata quella per il Dermatophagoides pteronyssinus. La prevalenza di ipersensibilizzazione verso Dermatophagoides pteronyssinus, Phleum pratense ed Olea europaea (olivo) ha mostrato una significativa relazione inversa con l’età. La concordanza tra i due test è risultata buona per Dermatophagoides pteronyssinus, Phleum pratense ed Olea europaea e moderata per Artemisia vulgaris (assenzio selvatico) e Parietaria judaica. Conclusioni: Il nostro studio ha evidenziato una prevalenza di atopia elevata, pari al 31-35,9% nei pazienti con DAC. Il confronto tra prick test ed IgE specifiche ha confermato la buona sovrapponibilità tra le due metodiche e la validità di entrambe nella diagnosi di atopia.